Peste Des Petits Ruminants of Goats, Outbreak and Economic Losses : A Case Study: PPR Outbreak in Goats (Biological Sciences - PJSIR, 2011)
In the determination of outbreak of peste des petits ruminants (PPR) and the economic losses caused by the disease 1392 distributed goats at Dimla thana of Nilfamari district, purchased from different markets, were studied during March, 2007 to May, 2007. Among the distributed goats, 54.7% died before treatment, 14.7% died after treatment and 30.6% survived after treatment. Survival rate was 67.51%. Maximum number (77.6%) of goats died before treatment in the flocks of Modhupur. Survival rate of the treated goats in the locally purchased flock was the highest (98.9%) whereas that in the goats purchased from Lalmonirhat was the lowest (34.3%). Survival percentage of the non-vaccinated goats was higher (71.60%) than that of the vaccinated goats (64.95%). Among the treated goats, 7.9% were pregnant, 4.4% of them aborted and 3.5% remained pregnant though they were infected. Infectious keratoconjunctivitis (IKC) was observed in 2.5% PPR infected goats. The total economic loss was estimated at Bangladesh Tk 10,16434 ($ 14520.49). Locally collected goats had the highest probability (80.6%) of survival after treatment whereas those collected from Rangpur had the highest probability (81.3%) of death before  treatment. Probability that the goats will die after treatment was the highest among the goats purchased from Lalmonirhat (59.5%). Survival of goats was significantly (P